Peran Social Capital dan Nilai-Nilai Lokal Dalam Reintegrasi Sosial Pascakonflik di Maluku (Studi di Siri Sori dan Siri Sori Amalatu Kecamatan Saparua – Kabupaten Maluku Tengah) - Eko Basuki; Korneles Balak; Nikel Nunuhuwae; Juvita Diana Feninlambir; Heril Lekipera; Petrus Parety; Kerotan Dwijangge (JURNAL BADATI, 2023)
The Siri Sori and Siri Sori Amalatu communities are indigenous peoples.The community experienced conflict in 2000 which resulted in the destruction of buildings such as people's houses, churches, schools, village government, baileo (custom home), and the deaths of the two conflicting communities.The social reintegration experienced by the Siri Sori and Siri Sori Amalatu people was chosen by researchers to be the object of research.This study uses a qualitative approach which is intended to understand and/or explore the phenomenon of post-conflict social reintegration in the Siri Sori and Siri Sori Amalatu communities.The purpose of this research is to obtain a conflict resolution model that can be used to assist communities and local governments (provinces, districts/cities) in Maluku in dealing with conflict resolution, especially local conflicts experienced by indigenous peoples in Maluku.In the social reintegration process, it turns out that social capital, local values, agent-structure, and the involvement of third parties have a very important role.